Investigation of heat resistance of metal oxide coatings on AISI 304 stainless steel - Shtefan, V. V.; Balamut, Nataliia; Kanunnikova, Nadiia; Kuznietsova, Anastasiia; Zuyok, Valeriy; Rostova, Hanna (My University, 2021)
Synthesized cathode Cr·CrOx and anodic FeOx metal oxide coatings on AISI 304 stainless steel. Their morphology and elemental composition have been studied. It was found that chromium-based oxide coatings increase the heat resistance of steel by 2-8 times and are resistant to temperatures of 1000 °C.
Keywords: stainless steel; metal oxide coating; heat resistance